Calcificação vascular intracraniana em pacientes idosos com doença renal crônica: relação com klotho - Carvalho, Luci Carla Dias Batista (2020)
Introduction: In view of the increase in life expectancy and the prevalence of diabetes and arterial hypertension, an increase in the elderly population with chronic kidney disease (CKD) has been observed. Vascular calcification is frequent in elderly and in patients with CKD. Some experimental studies have been observed a relationship between Klotho and vascular calcification. Thus, it is possible that Klotho is a risk factor for vascular calcification in patients with CKD. This study proposes the assessment of the association between intracranial vessel calcification and serum Klotho. Methods: This is a subanalysis of CTs performed in a study evaluating the association between cognition with markers of mineral and bone metabolism. We evaluated 60 CTs of patients with stages 4 and 5 CKD not on dialysis. Clinical, biochemical, and demographic data were collected. The CT was reported in a structured way, following the same sequence in all patients. Only vascular but not parenchymal calcification was evaluated. Results: Patients aged 81  7 years (65% men, 93% with hypertension, and 48% with diabetes). The median Klotho concentration was 783 (610, 994) pg/ml. Vascular calcification was observed in 18 patients (30%). Patients with intracranial vascular calcification were not distinguished from those without calcification regarding sex, age, body mass index, blood pressure, albumin, creatinine, cholesterol, calcium, phosphorus, and fibroblast growth factor 23. They had a slightly lower percentage of hypertension (83.3 vs. 96.6%, p = 0.042), and a lower concentration of Klotho [613 (509 - 805) vs. 824 (704, 1042), p = 0.009]. This difference remained significant even after adjusting for age, renal function, and classical cardiovascular risk factors such as diabetes, blood pressure, and cholesterol. Conclusion: Patients with moderate to severe CKD present intracranial vascular calcification in association with lower Klotho concentration.